Expression of the immune targets in tumor-infiltrating immunocytes of gestational trophoblastic neoplasia - Hongyan Cheng; Liju Zong; Liju Zong; Shuangni Yu; Jie Chen; Xirun Wan; Yang Xiang; Junjun Yang (Frontiers Media S.A., 2023)
Objectives: To evaluate the expression of emerging immune targets in the tumor-infiltrating immunocytes (TIIs) of human gestational trophoblastic neoplasia (GTN) specimens, and to analyze the correlation between the expression patterns and prognosis of GTN patients.Methods: Between January 2008 and December 2017, patients who were diagnosed histologically with GTN were included in this study. The expression densities of LAG-3, TIM-3, GAL-9, PD-1, CD68, CD8, and FOXP3 in the TIIs were assessed independently by two pathologists blinded to clinical outcomes. The expression patterns and correlation with patient outcomes were analyzed to identify prognostic factors.Results: We identified 108 patients with GTN, including 67 with choriocarcinoma, 32 with placental site trophoblastic tumor (PSTT), and 9 with epithelioid trophoblastic tumor (ETT). Almost all GTN patients showed expression of GAL-9, TIM-3, and PD-1 in TIIs (100%, 92.6%, and 90.7%, respectively); LAG-3 was expressed in 77.8% of the samples. The expression densities of CD68 and GAL-9 were significantly higher in choriocarcinoma than that in PSTT and ETT. The TIM-3 expression density in choriocarcinoma was higher than that in PSTT. In addition, the expression density of LAG-3 in the TIIs of choriocarcinoma and PSTT was higher than that in ETT. There was no statistical difference in the expression pattern of PD-1 among different pathological subtypes. The positive expression of LAG-3 in tumor TIIs was a prognostic factor for disease recurrence, and patients with positive expression of LAG-3 in the TIIs had poorer disease-free survival (p = 0.026).Conclusion: Our study evaluated the expression of immune targets PD-1, TIM-3, LAG-3, and GAL-9 in the TIIs of GTN patients and found that they were widely expressed but not associated with patients' prognoses, excepting the positive expression of LAG-3 was a prognostic factor for disease recurrence.